Nonsyndromic Unilateral Coronal Synostosis: A Comparison of Fronto-Orbital Advancement and Endoscopic Suturectomy. Issue 3 (March 2019) - Isaac, Kathryn V.; MacKinnon, Sarah; Dagi, Linda R.; Rogers, Gary F.; Meara, John G.; Proctor, Mark R.
Abstract : Background: Comparative effectiveness research is needed to optimize treatment of unilateral coronal synostosis. This study compares perioperative morbidity, ophthalmic, and aesthetic outcomes of patients with nonsyndromic unilateral coronal synostosis treated by endoscopic suturectomy or fronto-orbital advancement. Methods: From 2004 to 2015, patients with unilateral coronal synostosis were reviewed and data recorded for operative details, reoperations, and aesthetic results using the Whitaker classification, severity of strabismus, and need for surgical correction. Categorical data were analyzed using the Fisher's exact test and continuous data were analyzed using the Wilcoxon rank sum test. Results: Ninety-four patients were treated with endoscopic suturectomy ( n = 60) or fronto-orbital advancement ( n = 34). Median age at follow-up was 3.5 years (range, 1 to 9 years) for endoscopic suturectomy and 5.0 years (range, 2 to 11 years) for fronto-orbital advancement ( p = 0.06). The endoscopic suturectomy group had a lower operative time (42 minutes versus 216 minutes), length of stay (1 day versus 4 days), blood loss (25 cc versus 260 cc), and transfusion rate (0 percent versus 88 percent). Two patients treated with fronto-orbital advancement required secondary intervention for intracranial pressure. Thirty-one percent (16 of 52) of the endoscopic suturectomy group and 65 percent (19 of 29) of the fronto-orbital advancement group developed clinically significant strabismus requiring surgical repair ( p = 0.002). In the endoscopic suturectomy group, 88 percent (50 of 57) were Whitaker class I and 5 percent were class II. In the fronto-orbital advancement group, 41 percent (14 of 34) were class I and 44 percent class II. Need for bony revision (two of 57 versus three of 34) and need for secondary cranial procedure (two of 57 versus two of 34) were similar following endoscopic suturectomy and fronto-orbital advancement. Conclusions: For treatment of unilateral coronal synostosis, endoscopic suturectomy is associated with lower morbidity and comparable aesthetics. Patients treated with endoscopic suturectomy are half as likely to require strabismus surgery compared with those treated with fronto-orbital advancement. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.